“I want to be there. I have to be there.”: Parents’ perceived barriers and facilitators to bedside presence in the pediatric intensive care unit - Poole, Emily I.; Ryan, Molly; Walls, Martha; Slumkoski, Corey; Curran, Janet A.; Seabrook, Jamie A.; Foster, Jennifer R. (Frontiers in Pediatrics, 2024)
Introduction: Parental presence at the bedside during a stressful pediatric intensive care unit (PICU) admission may improve child comfort, reduce parental anxiety, and enable family engagement. We performed this study to identify factors that parents perceive impact their capability, opportunity, and motivation to be at the bedside in PICU. Methods: We conducted a qualitative descriptive study using semi-structured interviews based on the Theoretical Domains Framework (TDF). We included parents of children admitted to the PICU for at least 24 hours at IWK Health in Nova Scotia, Canada. Interviews were coded independently by two researchers using a directed content approach based on the TDF. We generated themes and subthemes, with the subthemes identified as factors impacting parental presence, and assigned TDF domains to each of the subthemes. Results: Fourteen primary caregivers (8 mother figures, 6 father figures) participated in 11 interviews. The factors associated with parental presence were captured by 6 themes: Understanding the Medicalized Child; Maintaining the Parent Role; Life Beyond the Hospital; Parental Intrinsic Responses and Coping; Support Structures; and The PICU Environment. Fifty-two barriers and enablers were identified within 13 TDF domains; 10 TDF domains were determined to be relevant to parental presence, which may be used to guide design of future interventions. Participants emphasized the importance of self-care to enable them to remain physically at their child’s bedside and to be engaged in their care. Conclusions: Parents perceive multiple factors within 6 themes act as barriers or enablers to presence with their critically ill child in the PICU. Guided by relevant TDF domains, interventions may be designed to optimize presence, particularly engaged presence, which may improve health-related outcomes of children and their parents.